DAKWAH QASIDAH MODEREN AL-FALAH MELALUI MUSIK - Asep Kurniawan (ORASI: Jurnal Dakwah dan Komunikasi, 2018)
So far da'wah is generally carried out traditionally, i.e. through religious lectures at worship places. This da'wah seems to be focused and preserved. As a result, the target of da'wah does not reach many people especially young people, who need something new and in accordance with their world. For this reason, with the presence of the Modern Qasidah al-Falah gives a new nuance to da'wah, which can be accepted by many young people, because it is presented through musical activities. The purpose of this research is to reveal in depth how far dawah of Modern Qasidah al-Falah through music. The research approach is qualitative. The instruments of collecting data are in-depth observation, in-depth interviews and documentation. The Techniques of analysing data are collecting data, reducting data, displaying data, and conclusing data. The research found that modern qasidah al-Falah music was a combination of elements of modern music while maintaining its Islamic characteristics, those were song lyrics, which were full of invitation to kindness. Dawah of Modern Qasidah al-Falah through music was carried out in many da'wah areas. The positive impact of this activity was specifically the change in the behavior of its members to good behaviour. Thus, the dawah of Modern Qasidah al-Falah through music is a new breakthrough for the development of da'wah in order to be accepted by more segmentation of society.